Eliot Ness : the rise and fall of an American hero - Perry, Douglas, 1968- (Viking, 2014)
A wide-ranging portrait of the legendary leader of the Untouchables traces his years after his famous confrontation with Al Capone, documenting his efforts to end corruption in Cleveland and his achievements throughout the Torso Murderer case.